Tsunami inundation maps for the northwest of Peninsular Malaysia and demarcation of affected electrical assets - Naim N.N.N.; Mardi N.H.; Malek M.A.; Teh S.Y.; Wil M.A.; Shuja A.H.; Ahmed A.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Coastal zones; Tsunamis; Coastal change; Coastal communities; Development planning; Inundation maps; Moment magnitudes; Topographic data; Tsunami inundation; Tsunami simulation; Floods; coastal zone management; early warning system; earthquake event; electricity supply; flooding; map; risk assessment; safety; tsunami event; wave modeling; wave runup; Aceh; Andaman Sea; article; earthquake; Penang; seashore; simulation; tsunami; environmental monitoring; Indonesia; Malaysia; tsunami; Andaman Sea; Indian Ocean; Java Trench; Malaysia; West Malaysia; Areca catechu; Earthquakes; Environmental Monitoring; Indonesia; Malaysia; Tsunamis